Implementation of The Beta Method in Moral Learning Imam Al Ghozali's Perspective on Including Children - Esy Clever Insani Wijianti; Machnunah Ani Zulfah (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This study aims to determine the implementation of the concept of moral education from the perspective of Imam al-Ghazali in forming character, to find out the efforts in implementing the concept of moral education from the perspective of Imam al-Ghazali in forming character, and to find out the advantages and disadvantages of implementing the concept of moral education from the perspective of Imam al-Ghazali in forming character in At-Thahiriyah Islamic Boarding School. The research method used in this study is a descriptive qualitative research method using field studies at Pondok Pesantren At-Thahiriyah Kaloran, Serang City. Data collection techniques using observation, interviews, and documentation. From the results of the study it can be concluded that the implementation of the concept of moral education from the perspective of Imam al-Ghazali has mostly led to the formation of the character of the santri. Efforts were made in implementing the concept of moral education from the perspective of Imam al-Ghazali in shaping the character of the students, namely: setting an example, applying habituation, always reminding them by giving advice, telling stories or stories during recitation or when there is class, giving rewards and punishments to students. students when they are wrong, as well as activities of students and scheduled worship as a form of effort by Islamic boarding schools. The advantages are that the morals of the santri become more focused, the condition of the Islamic boarding school becomes orderly, an increase in the sense of trust from the ustadz or ustadzah, can better distinguish between right and wrong. And the drawbacks are the worldly nature, and the varied character of the santri